PENGEMBANGAN MODUL PEMBELAJARAN DINAMIKA PARTIKEL YANG TERINTEGRASI DENGAN ALAT EKSPERIMEN BERBASIS MIKROKONTROLER ARDUINO UNTUK SISWA SMA - Naila Fauza; Mustofa; Dedi Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teaching particle dynamics requires innovative teaching materials to facilitate student learning. This study aims to determine the validity and practicality of particle dynamics learning modules integrated with microcontroller-based experimental tools. The research and development methods used in this study use the ADDIE model, including analysis, design, development, implementation, and evaluation. The instruments used are validity sheets and practicality sheets. The results of the research and development of the particle dynamics learning module integrated with microcontroller-based experimental tools showed an average total validity score of 0.9, categorized as valid, and an average practicality score of 3.8, categorized as practical. Based on the results, the rotation dynamics learning module integrated with microcontroller-based experimental tools is suitable for use.